TRAINING FOR MITIGATION OF PLANNED BANDS AND LONG-RANGE FIELDS IN THE THREAT OF WRECKAGE - Eldessa Vava Rilla, Eldessa Vava Rilla; Herlin Rusyani, Herlin Rusyani; Andhika Lungguh Perceka, Andhika Lungguh Perceka; Gin Gin Sugih Permana, Gin Gin Sugih Permana (LP4M STIKes Karsa Husada Garut, 2023)
Increasing the capacity of the public in disaster risk reduction is not a social movement that is cashistic, temporary, reactive and focused on impact management alone, but encourages disaster risks reduction as a basic policy and development strategy that is integrated into every policy and planning, including development budgets at all levels. The ability of a society to cope with the risks of both natural and social disasters is vital, because by having the ability of hatred, one can know what to do and what to avoid to reduce the negative consequences of the disaster that occurs. The lack of community capacity in disaster mitigation can increase the risk of disasters, especially if the community does not participate in efforts to reduce the risks of damage caused, such as physical damage and loss of human life.